Deprivation of liberty in the system of measures of criminal legal impact: systemic and functional analysis of the legal status in the norms of the Belarusian criminal legislation - Shidlovsky, Andrey V. (Journal of the Belarusian State University. Law, 2023)
The legal status of deprivation of liberty in the norms of the Belarusian criminal legislation is analysed through a system-functional dimension in comparison with criminal law institutions and other legal provisions. The evolution of punishment in the form of deprivation and its place in the system of measures of criminal law influence are studied. The conclusion about the complex nature of the legal status formation of deprivation of liberty is made, and on this basis, the differentiation of the elements that form it is carried out depending on their functional purpose, influence on the content and nature of the origin of other legal institutions and measures of criminal law impact. It is substantiated that the legal nature of deprivation of liberty is formed by a complex of criminal law, penitentiary and criminal procedure norms and institutions. The legal regulation of deprivation of liberty as a measure of penal liability is not limited to criminal law rules on the procedure for its appointment or other application. This measure is associated with a complex of regulatory norms of the penitentiary and criminal procedural legislation. The complex legal status of deprivation of liberty, including the norms of related industries and sub-sectors of legislation, makes it possible to speak of a penitentiary type of criminal liability of a resocialisation and rehabilitation nature. In the current criminal legislation, the phenomenon of deprivation of liberty combines its two fundamentally different legal statuses: as a lawful phenomenon and as an illegal phenomenon.